2019
DOI: 10.3347/kjp.2019.57.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Tm-shift Method for Detection of Cat-Derived Hookworms

Abstract: Melting temperature shift ( T m -shift) is a new detection method that analyze the melting curve on real-time PCR thermocycler using SYBR Green I fluorescent dye. To establish a T m -shift method for the detection of Ancylostoma ceylanicum and A. tubaeforme in cats, specific primers, with GC tail of unequal length attached to their 5′ end, were designed based on 2 SNP loci (ITS101 and ITS296) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This study is the first report of A. tubaeforme in Thailand. A. tubaeforme is widely distributed including Australia, Brazil, Italy, Qatar, Spain, the United States of America and China (Fu et al, 2019b). Clinical signs of A. tubaeforme infection depends on the dose of infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is the first report of A. tubaeforme in Thailand. A. tubaeforme is widely distributed including Australia, Brazil, Italy, Qatar, Spain, the United States of America and China (Fu et al, 2019b). Clinical signs of A. tubaeforme infection depends on the dose of infection.…”
Section: Discussionmentioning
confidence: 99%
“…This study also firstly reported A. tubaeforme in Thailand. A. tubaeforme is widely distributed including Australia, Brazil, Italy, Qatar, Spain, the United States of America and China (Fu et al, 2019b). Heavy A. tubaeforme infection results in decreasing pack cell volume and hemoglobin rapidly causing anemia suggesting that the hookworm positive cats should not be neglected.…”
Section: General Discussion Conclusion and Further Recommendationsmentioning
confidence: 99%